Current therapeutics and future perspectives of immunotherapy through Chimerics Antigens Receptors (CARs) in T cells in the treatment of Human Immunodeficiency Virus (HIV) infection: A systematic review (Research, Society and Development, 2025)
Antiretroviral Therapy (ART) controls HIV but does not eradicate the virus, requiring lifelong treatment. CAR-T (Chimeric Antigen Receptor) immunotherapy emerges as a promising therapeutic approach. The objective was to analyze the current evidence, limitations, and future perspectives of CAR-T immunotherapy for HIV. This is a systematic review following the PRISMA2020 guidelines and the SWIM protocol; the search was conducted in the PubMed, Embase, Scopus, and Web of Science databases, with complementary searches on the ScienceDirect, Nature, and ClinicalTrials platforms, for the period of 2020 to 2025. After applying inclusion and exclusion criteria, 25 articles were selected. Significant advances in the design of CAR-T cells for HIV, such as DuoCAR-T and those based on broadly neutralizing antibodies (bNAbs), have increased in vivo efficacy and have countered viral escape. The protection of CAR-T cells with C34-CXCR4 and CCR5 inhibitors proved crucial in persistence and antiviral effect. The use of Rapamycin to reverse cellular exhaustion and the Nef protein to mitigate allogeneic immune rejection were also investigated. Despite success in reducing the viral reservoir, challenges remain, including the diversity of the viral envelope, access to anatomical sanctuaries, and treatment safety. The future of the therapy, which has great potential, focuses on combining multispecific CARs with Latency-Reversing Agents (LRAs) to improve persistence, targeting, and safety. However, more robust clinical trials are needed to validate its application and expand its efficacy.